Comparison of MR Imaging and Dual-Energy CT for the Evaluation of Cartilage Invasion by Laryngeal and Hypopharyngeal Squamous Cell Carcinoma - Kuno, H.; Sakamaki, K.; Fujii, S.; Sekiya, K.; Otani, K.; Hayashi, R.; Yamanaka, T.; Sakai, O.; Kusumoto, M. (American Journal of Neuroradiology, 2018)
BACKGROUND AND PURPOSE: Dual-energy CT can distinguish iodine-enhanced tumors from nonossified cartilage and has been investigated for evaluating cartilage invasion in patients with laryngeal and hypopharyngeal squamous cell carcinomas. In this study, we compared the diagnostic accuracy of MR imaging and of a combination of weighted-average and iodine overlay dual-energy CT images in detecting cartilage invasion by laryngeal and hypopharyngeal squamous cell carcinomas, in particular thyroid cartilage invasion.MATERIALS AND METHODS: Fifty-five consecutive patients who underwent 3T MR imaging and 128-slice dual-energy CT for preoperative initial staging of laryngeal or hypopharyngeal squamous cell carcinomas were included. Two blinded observers evaluated laryngeal cartilage invasion on MR imaging and dual-energy CT using a combination of weighted-average and iodine-overlay images. Pathologic findings of surgically resected specimens were used as the reference standard for evaluating sensitivity, specificity, and the areas under the receiver operating characteristic curve of both modalities for cartilage invasion by each type of cartilage and for all cartilages together. Sensitivity and specificity were compared using the McNemar test and generalized linear mixed models.RESULTS: Dual-energy CT showed higher specificity than MR imaging for diagnosing all cartilage together (84% for MR imaging versus 98% for dual-energy CT, P < .004) and for thyroid cartilage (64% versus 100%, P < .001), with a similar average area under the curve (0.94 versus 0.95, P = .70). The sensitivity did not differ significantly for all cartilages together (97% versus 81%, P = .16) and for thyroid cartilage (100% versus 89%, P = .50), though there was a trend toward increased sensitivity with MR imaging.CONCLUSIONS: Dual-energy CT showed higher specificity and acceptable sensitivity in diagnosing laryngeal cartilage invasion compared with MR imaging.AUCarea under the curveIOiodine overlayROCreceiver operating characteristicSAFIREsinogram-affirmed iterative reconstructionSCCsquamous cell carcinomaWAweighted-average